PROGRAM LAYANAN BIMBINGAN DAN KONSELING DALAM MEMPERSIAPKAN TENAGA KERJA LULUSAN SMK: SEBUAH KAJIAN LITERATUR - Lika; Firman; Neviyarni (Conseils : Jurnal Bimbingan dan Konseling Islam, 2024)
This research was essentially conducted to understand the Guidance and Counseling Service program in vocational high schools (SMK). It further discusses the importance of the Guidance and Counseling Service program in SMK, the depiction of the Guidance and Counseling Service program in schools, and alternative models of the Guidance and Counseling Service program in SMK. This research is a literature review study sourced from various writings such as books and research articles. The obtained sources were then analyzed to see their relevance to the research objectives. It was found that the Guidance and Counseling Program is essential, especially in SMK. The depiction of the Guidance and Counseling Service program indicates that the Guidance and Counseling Program should also be based on several other analyses besides the students' needs. Furthermore, there are several alternative models in the Guidance and Counseling Service program that can be further researched regarding the suitability and accuracy of the planning model with the conditions in schools.